(untitled) (Journal of Economic Research & Business Administration, 2016)
The article discusses the theoretical and methodological aspects of the territorial organization of agriculture. The authors examine a number of theories, which cover certain aspects of the territorial distribution of agricultural industries, and studying its individual or specific issues (eg, the impact of agricultural land relative locations of the city (market) on the yield and specialization of agriculture). Revealing the essence of these theories, the authors note that the inclusion of the underlying principles of these theories make it possible to effectively use agricultural production factors. The main task of the territorial organization of a mutual adaptation of agricultural production areas and production, creation of favorable conditions for effective space management through efficient deployment of the organization of production and use of production factors. Highlighted the concept of adaptive intensification of agriculture, which is characterized by a complex effect of natural, social, economic and technological factors on the territorial system of agriculture. This theory implies a differentiated approach to the spatial distribution of agricultural production, depending on the combination of natural and socio-economic conditions.